2023
DOI: 10.3390/pr11030703
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in Kaolinite Flotation Using Dodecylamine: Experiment and DFT Study

Abstract: The molecular structure of cationic surfactants is closely related to their flotation performance. In this paper, three cationic surfactants with different head group structures were selected as collectors of kaolinite, and the substituent effects were studied by the DFT method. The DFT calculation results showed that increasing the number of substituents in the dodecylamine head group can significantly increase its surface and head group charge. Dodecylamine has the lowest LUMO orbital energy, so dodecylamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that the collecting capacity of three reagents is BHOM > BHUA > CMCA, and the interaction between the O and N atoms of the BHUA and H atoms of kaolinite is realized through the formation of hydrogen bonds. Shen et al [177] studied the substituent effect of three cationic collectors (DDA, dodecyl diethanolamine, and dodecyl dihydroxyethyl methyl ammonium chloride (BHMAC)) with different head group structures for kaolinite flotation using the DFT approach. The calculated results deduced that the increase in the number of substituents in the dodecylamine head group can significantly increase its Connolly surface, head group charge and solvent-accessible surface, which is conductive to decreasing the collector consumption.…”
Section: Kaolinitementioning
confidence: 99%
“…The results showed that the collecting capacity of three reagents is BHOM > BHUA > CMCA, and the interaction between the O and N atoms of the BHUA and H atoms of kaolinite is realized through the formation of hydrogen bonds. Shen et al [177] studied the substituent effect of three cationic collectors (DDA, dodecyl diethanolamine, and dodecyl dihydroxyethyl methyl ammonium chloride (BHMAC)) with different head group structures for kaolinite flotation using the DFT approach. The calculated results deduced that the increase in the number of substituents in the dodecylamine head group can significantly increase its Connolly surface, head group charge and solvent-accessible surface, which is conductive to decreasing the collector consumption.…”
Section: Kaolinitementioning
confidence: 99%